Verminous meningoencephalomyelitis in a red kangaroo associated with Angiostrongylus cantonensis infection. (January 2022) - Patial, Sonika; Delcambre, Brooke A.; DiGeronimo, Peter M.; Conboy, Gary; Vatta, Adriano F.; Bauer, Rudy
Angiostrongylus cantonensis is a zoonotic parasitic helminth that normally resides in the pulmonary arteries and the right ventricle of rats ( Rattus sp.), the definitive host, where it causes little disease. Humans, dogs, opossums, and various zoo animals are "accidental" hosts. Here we report verminous meningoencephalomyelitis caused by A. cantonensis in a 9-mo-old male red kangaroo ( Macropus rufus ). The kangaroo was first presented lethargic, recumbent, and hypothermic, with severe muscle wasting. Within 3 wk, he progressed to non-ambulatory paraparesis and died. Gross examination revealed multifocal areas of dark-brown discoloration, malacia, and cavitation in the brain and the spinal cord. Histologically, there were several sections of nematodes surrounded by extensive areas of rarefaction, hemorrhage, spongiosis, neuronal necrosis, and gliosis. Based on size, morphology, and organ location, the nematodes were identified as subadult males and females. Interestingly, an eosinophilic response was largely absent, and the inflammatory response was minimal. A. cantonensis infection had not been reported previously in a red kangaroo in Louisiana or Mississippi, to our knowledge. Our case reaffirms the widespread presence of the helminth in the southeastern United States and indicates that A. cantonensis should be considered as a differential in macropods with neurologic clinical signs in regions where A. cantonensis is now endemic.